Modelado acústico a través de métodos numéricos para la generación de propuestas de intervención en aulas de clase (2018)
The work below consist of the generation of intervention proposals in architectural acoustics for classrooms in public institutions in the colombian cities Medellín, Bogotá and Cali under the project: Identificación de factores de desempeño ambiental (acústico, térmico y visual) determinantes de la salud mental de docentes y estudiantes de escuelas públicas en Bogotá, Medellín y Cali: Línea base para el análisis de la política pública según la norma NTC 4595. For this end a 14 classrooms sample was taken distributed in the three cities mentioned before. The work is divided in three phases and its results are based in geometric acoustics simulations in CATT-Acoustics v.9. The first phase aims to give an initial acoustics diagnosis for each one of the classrooms using simulations. It was found that In the most part of the classrooms the objectives proposed by this investigation were not accomplished: Reverberation time less than 1 second ant STI values greater than 0,6. The second phase take simulation results and with this data and architectural analysis of the classroom (geometry and materiality) gives an architectural proposal in the walls which aims to increase the room’s absorption by adding absorbent panels. In the third phase new simulations are done, this time with the intervention proposal. This simulation let the investigation to verify that the intervention works and works for the most of the rooms